Domestic measures during peace time for the implementation of International Humanitarian Law (IHL) - Islam, Mohammad Saidul (IIUC Studies, 2017)
International Humanitarian Law (IHL) is frequently neglected by the Parties to the Geneva Conventions during armed conflict (AC). In the contemporary world, IHL has been facing a great threat due to lack of proper implementation which resulted in the severe wounds, unnecessary sufferings, superfluous injury, and even death to the civilians, children, women, and combatants in and outside the armed field. For the implementation of IHL, it is essential that States must take proper steps during peace, conflict, and post-conflict time. The article presents the various mechanisms of implementation of IHL need to be taken by the States during the time of peace. It also focuses the most significant peace time steps sought to be taken by the State to make the IHL rules familiar to the civilians and combatant, to ensure the availability of the necessary instrumentalities for using those during AC for protection and minimization of the sufferings of the victims and to enact essential legislation for trial of the violators after the end of the conflict. IIUC Studies Vol.14(2) December 2017: 111-126